LA SALUD OCUPACIONAL EN LA ACTIVIDAD LABORAL DE LOS TRABAJADORES MINEROS DEL BARRIO PUENTE DE BUZA DE LA PARROQUIA MULUNCAY DEL CANTÓN ZARUMA PROVINCIA DE EL ORO Y LA INTERVENCIÓN DEL TRABAJADOR SOCIAL - Añazco Loayza, Dayana Carolina (2018)
The present research was carried out in “Puente de Buza” neighborhood in El Oro province, in the same research had participation mining workers of the parish, president of the parish board, a representative of "Reina del Cisne 1" mine; In order to verify the existence of the causes that affect the health of the mining workers. For this, it was necessary to establish the theoretical and scientific basis of the study object through its categories, then determined the various types of occupational diseases that are presented in the mining processes, and finally, a preventive action plan for health occupational promotion and labor development of the miners of the Muluncay parish. The methodology applied to the research was approached through the scientific method, inductive-deductive and statistical, the sample that was taken was 30 workers, its approach was quantitative-qualitative; The instrument used was the survey in which a questionnaire was applied with open and closed questions for elements which have a mayor relevance. The information of the data allowed to determine that the diseases of mayor importance are silicosis, deafness, tendinitis, caused by the lack of personal protection equipment (epp), necessary to work and for the inappropriate use of epp. While the most frequent accidents are cuts, eye irritation, minor fractures, sprains, etc. With direct affectation to their health this research has as an object to generate a plan of action to prevent and protect the health of miners in the parish in order to improve their quality of life in the work that they perform daily, avoiding risks and accidents